2006
DOI: 10.1007/s10488-006-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Doing the Difficult and Dangerous: The Community Program Practice Scale

Abstract: The CPPS uses staff respondents to portray practices and program climate of nonresidential mental health programs. We report psychometric analyses of 1,533 respondents in 165 programs. Confirmatory factor and partial credit analyses identified eight practice and five climate subscales, all of which show adequate psychometric properties. Program types are distinguished better by practices (R (2) values .37 to .52) than by climate (R (2) values .09 to .23), as expected. Multiple discriminant analysis and K-means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Staff and member evaluations were concordant on 68% of the environmental domains, with the highest level of agreement occurring in the PES domain assessing the emotional, psychological, and interpersonal climate of the program milieu, which provides some indication of overall program quality (Hargreaves et al 2007). Across all program areas, staff ratings of the environment were slightly higher than those of members, but only significantly different in six specific areas.…”
Section: Comparing Staff and Member Evaluations Of The Program Enviromentioning
confidence: 87%
See 3 more Smart Citations
“…Staff and member evaluations were concordant on 68% of the environmental domains, with the highest level of agreement occurring in the PES domain assessing the emotional, psychological, and interpersonal climate of the program milieu, which provides some indication of overall program quality (Hargreaves et al 2007). Across all program areas, staff ratings of the environment were slightly higher than those of members, but only significantly different in six specific areas.…”
Section: Comparing Staff and Member Evaluations Of The Program Enviromentioning
confidence: 87%
“…Thus, attempts to describe services or practices, and evaluate the environments of mental health programs have been touted as venturing into the ''difficult and dangerous'' due to a lack of theory-driven approaches and overreliance on nonconsumers to describe services (Bickman 2000). Hargreaves et al (2007), however, have demonstrated that these environments can indeed be successfully described as well as distinguished from one another by comparing underlying goals and concrete practices. However, the authors warn, evaluations based solely on a program's climate do not guarantee accuracy about the services provided, but when program climate indicators are poor they can ''raise questions about quality and program implementation (p.…”
Section: Staff and Member Perceptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PES is a cross-model practice measure that has been used in assessing common elements across a variety of community based psychiatric programs (Hargreaves et al 2007). The PES also assesses practices that contribute to the program's emotional and psychological climate as well as those that reflect core program philosophy and values such as empowerment and staff-member relations.…”
Section: Program Environmentmentioning
confidence: 99%